2013
DOI: 10.1097/aog.0b013e3182999085
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Massage to Reduce Blood Loss After Vaginal Delivery

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The flow of study identification is shown in Figure S1. Three RCTs, including 3842 singleton gestations, were found comparing uterine massage, in addition to oxytocin and controlled cord traction, versus no uterine massage . Statistical heterogeneity within the studies was high with I 2 = 73% for the primary outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow of study identification is shown in Figure S1. Three RCTs, including 3842 singleton gestations, were found comparing uterine massage, in addition to oxytocin and controlled cord traction, versus no uterine massage . Statistical heterogeneity within the studies was high with I 2 = 73% for the primary outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Different strategies have been published to prevent PPH . Active management of the third stage of labour consists of a group of interventions, including administration of prophylactic oxytocin at or after the delivery, cord clamping and cutting, controlled cord traction to deliver the placenta, and uterine massage . These interventions should be evaluated individually for efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane review [1] summarized the benefits and risks of AMTSL and concluded that although there is a lack of high-quality evidence, AMTSL reduced the risk of hemorrhaging > 1,000 mL at the time of birth in a population of women with a mixed risk of excessive bleeding. Regarding cord traction [24] and uterine massage [5, 6], the effects of reducing maternal blood loss have been controversial. In addition, the most common cause of PPH is uterine atony, which complicates 1 in 20 deliveries and is responsible for 80% of PPH cases [7].…”
Section: Introductionmentioning
confidence: 99%
“…1 The raised question is whether those women needing therapeutic oxytocics in our study should have been randomized to therapeutic oxytocic alone or to uterine massage plus therapeutic oxytocic. In Reply: We thank Dr. Fröhlich for his interest in our recent publication pertaining to the effectiveness of routine uterine massage to reduce blood loss after vaginal delivery.…”
mentioning
confidence: 99%
“…I read with interest the article by Chen et al 1 Postpartum hemorrhage is indeed a serious complication of labor all over the world. Postpartum hemorrhage needs to be dealt with promptly, efficiently, and comprehensively.…”
mentioning
confidence: 99%